Training program on creative strategies to manage the teaching of language course and musical perception (Mayéutica Revista Científica de Humanidades y Artes, 2015)
The study aimed to design a training program on Creative Strategies to Manage the Teaching of the subject Language and Musical Perception I, at UPEL - IPB. It was built from a positivist vision with quantitative approach, in the form of feasible project, supported by a descriptive field research. It was developed in three phases: Phase I. Diagnostic Study, in which the need to design the program was determined; for this purpose, they were taken as subjects of study 10 teachers Musical Education Department of the institution under study and answered a questionnaire type instrument. The validity of the content of the instrument was determined by the technique of expert judgment and the analysis of the results was performed by descriptive statistics percentage. Phase II: Feasibility Study, in which the feasibility, market, technical, financial and legal was determined. The results of Phase I and Phase II allowed to determine the need and feasibility of the program, which carried to the Phase the III: correspondent to the design of the Program. Likewise, there was realized a body of conclusions and recommendations that indicate that a training program does not exist in the institution for teachers on creative strategies that enable them to acquire the theoretical - practical knowledge that they need and in addition it allowed to detect the lack of knowledge that the teachers have on the topic in study, for which the offer must be considered for the authorities of the institution.
Keywords: teaching process; teaching techniques; language and musical perception; training program